PENGEMBANGAN MEDIA WEBSITE LINKTREE DALAM MENULIS TEKS PROSEDUR PADA SISWA KELAS 5 SDN 3 TAPA KABUPATEN BONE BOLANGO - Sekar Sari Wulandari; Rusmin Husain; Fidyawati Monoarfa; Wiwy T. Pulukadang; Sukri Katili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to develop a Linktree-based website digital learning medium for Indonesian language instruction on procedural texts for fifth-grade students at SDN 3 Tapa, Bone Bolango Regency. This study employed a Research and Development (R&D) approach using the 4D model, which consists of four stages: define, design, develop, and disseminate. Data were collected through observation, questionnaires, and documentation. The define stage was conducted to analyze learning needs and identify problems in teaching procedural text writing. The design stage involved developing the content structure and interface of the Linktree website, which included the menus User Guide, Learning Materials, Student Worksheets (LKPD), and Evaluation. The develop stage comprised validation by media experts, subject-matter experts, and teachers as users, as well as field testing with students. The validation results indicated an average feasibility level of 89.16%, which falls into the “very feasible” category. The practicality of the media based on student responses reached 87.88%, categorized as “very practical.” The effectiveness of the media was measured by comparing pre-test and post-test scores, showing an increase from a mean pre-test score of 56 to a post-test score of 84.23, representing an improvement of 28.23 points. The N-Gain value of 0.64 (64%) indicates a moderate (fairly effective) level of effectiveness. Therefore, it can be concluded that the Linktree-based digital learning media is highly feasible, highly practical, and sufficiently effective in improving procedural text writing skills among fifth-grade students at SDN 3 Tapa, Bone Bolango Regency.